The Postembryonic Development of the Ocellar System of Triatoma infestans Klug (Heteroptera: Reduviidae) - Insausti, T.C. (2000)
Simple eyes or ocelli coexist with compound eyes in many adult insects. The change in the morphology of the ocelli along the five larval instars of Triatoma infestans was studied by light and scanning electron microscopy. Our analysis showed that the development of the ocelli of these bugs occurs gradually along the larval life. The photoreceptor layer is present from the second-instar onwards. The cornea appears first at the imaginal stage and grows up to the 18-20th day after the last ecdysis, associated to an increase in the retinal mass. Findings are discussed in a comparative fashion and in relation to the functionality of the ocellar system in T. infestans.